Issues of modernizing education, healthcare, and employment sectors to ensure a prosperous life - Hasanov, Rajabboy (Goodwood Publishing, 2024)
Purpose: This study examines the vertical alignment of digital innovation between secondary and higher education in Uzbekistan, focusing on how digitized STEM curricula at the school level correspond to digital transformation initiatives in universities. Research methodology: This study analyzes recent reforms in Uzbekistan’s education, healthcare, and employment sectors through content analysis, statistical review, and comparative approaches. It also evaluates international best practices and proposes interconnected indicators to assess prosperity based on economic opportunities, personal freedom, and social justice. Results: Reforms have improved medical infrastructure, digital health services, job creation, and entrepreneurship. Nevertheless, challenges remain in ensuring equitable access to quality healthcare and addressing the high levels of informal employment. Bridging the gap between educational outcomes and labor market demands, as well as expanding medical insurance and preventive care, are identified as priorities for sustainable welfare. Conclusions: Uzbekistan has implemented key reforms in education, healthcare, and employment to enhance societal well-being, emphasizing digital innovation, infrastructure development, and job creation. While progress is evident, systemic challenges such as informal employment, uneven medical service quality, and mismatches between education and labor market needs persist. Addressing these issues and ensuring consistent reform implementation are essential for building a prosperous, educated, and healthy society. Limitations: This study is limited by its descriptive scope, focusing on policy directions and reform outcomes without an in-depth empirical assessment or long-term evaluation. Contribution: This study highlights the interconnectedness of education, healthcare, and employment reforms, contributing to the discourse on integrated social reform and improved national well-being.